Thermal and Physical Properties of Pt Nanorods - Mirabi, A.; Gilaki, M.; Ghorbani, H.; Shokuhi Rad, A.; Binaeian, E. (Asian Journal of Chemistry, 2011)
Optically resonant metal nanoparticles have become an increasingly popular tool in the various areas. Due to their near-infrared (NIR) optical properties, these metal nanoparticles are compatible with modalities such as in vitro optical microscopy. Platinum nanorods display crossways and longitudinal exterior plasmon resonances to facilitate electron oscillations at 90º angle and parallel to the rod duration path, in that order and their longitudinal exterior plasmon wavelengths (LEPWs) are fine from the visible to infrared area. Their absorption side view are at least 5 orders bigger than folks of conservative colourings and the light dispersion by Pt nanorods is numerous orders better than the light discharge from powerfully fluorescent colouring.